2005
DOI: 10.1098/rspb.2005.3114
|View full text |Cite
|
Sign up to set email alerts
|

Spider webs designed for rare but life-saving catches

Abstract: The impact of rare but positive events on the design of organisms has been largely ignored, probably due to the paucity of recordings of such events and to the difficulty of estimating their impact on lifetime reproductive success. In this respect, we investigated the size of spider webs in relation to rare but large prey catches. First, we collected field data on a short time-scale using the common orb-weaving spider Zygiella x-notata to determine the distribution of the size of prey caught and to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 25 publications
(37 reference statements)
5
107
0
Order By: Relevance
“…Even if chances for a single prey of being caught are indeed small (e.g., between 3.5% and 4.8%; Morse 1979, Reader et al 2006, Brechbü hl et al 2010a, the chances for a spider to catch a prey are rather large, approximately one prey individual within a day (on average one prey individual every 10.8 hours: 10 hours of observations per day 3 3 experimental days 3 28 replicates/78 prey caught). Given the low metabolic rate of spiders, one prey of intermediate size per day might be sufficient for survival, however reproduction requires the rare incidence of catching a large prey (Venner and Casas 2005). Hence, the high abundance of prey and the low metabolic rate may make up for the low probability of successfully attacking a prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if chances for a single prey of being caught are indeed small (e.g., between 3.5% and 4.8%; Morse 1979, Reader et al 2006, Brechbü hl et al 2010a, the chances for a spider to catch a prey are rather large, approximately one prey individual within a day (on average one prey individual every 10.8 hours: 10 hours of observations per day 3 3 experimental days 3 28 replicates/78 prey caught). Given the low metabolic rate of spiders, one prey of intermediate size per day might be sufficient for survival, however reproduction requires the rare incidence of catching a large prey (Venner and Casas 2005). Hence, the high abundance of prey and the low metabolic rate may make up for the low probability of successfully attacking a prey.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative interpretation would be that predators with an over-supply of a variety of prey do not need to be picky in their diet or sophisticated in their strategy. The abundance of suitable prey would ensure sufficient nourishment for growth and reproduction (Venner and Casas 2005). This should apply particularly to predators with low metabolic rates, such as invertebrate sit-and-wait predators, which can afford to suppress foraging for long times and many prey encounters.…”
Section: Discussionmentioning
confidence: 99%
“…As cursorial prey items were larger and potentially more nutritious than aerial prey items, we hypothesize that the posterior median eyes are the result, at least in part, of selection for increased diet breadth-the ability to incorporate larger, more nutritious cursorial prey. It has been suggested that web-building spiders depend on rare, large prey items to survive and produce eggs ( [18,19]; but see [20]); thus the unique foraging tactics and specialized visual capabilities of Deinopis spiders might increase their ability to capture higher quality prey items typically out of reach of the average web-building spider. Indeed, recent phylogenetic analyses suggest that this net-casting technique arose in parallel with a vastly increased abundance of cursorial insect prey during the Cretaceous Terrestrial Revolution [21].…”
Section: Discussionmentioning
confidence: 99%
“…The size and/or mass of an entangled insect may elicit vibrations in the radial silks of a specific frequency that provide information to the spider about the prey (Landolfa and Barth, 1996) that, consequently, affects web architecture (Nakata, 2009), creating a phenotype-environment positive feedback cycle. As spiders build webs aimed to capture the largest and/or most nutritionally profitable prey available in their habitat (Venner and Casas, 2005), the vibratory cues of the largest prey may be used to design webs aimed at catching those prey. However, due to the correlated nature of most prey attributes no study, to date, has manipulated the mass and size of different prey to investigate the nutritional and nonnutritional consequences on spider orb-web architectural plasticity without undue manipulation of nutritional factors.…”
Section: Introductionmentioning
confidence: 99%